2023
DOI: 10.3389/fimmu.2022.997115
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid receptor 2 plays a pro-tumorigenic role in non-small cell lung cancer by limiting anti-tumor activity of CD8+ T and NK cells

Abstract: Cannabinoid (CB) receptors (CB1 and CB2) are expressed on cancer cells and their expression influences carcinogenesis in various tumor entities. Cells of the tumor microenvironment (TME) also express CB receptors, however, their role in tumor development is still unclear. We, therefore, investigated the role of TME-derived CB1 and CB2 receptors in a model of non-small cell lung cancer (NSCLC). Leukocytes in the TME of mouse and human NSCLC express CB receptors, with CB2 showing higher expression than CB1. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 76 publications
(119 reference statements)
0
7
0
Order By: Relevance
“…Flow cytometry and fluorescent microscopy analysis confirmed that NK cells express high CB2 protein levels, albeit showing a considerable variability among donors [22]. A similarly high CB2/CB1 ratio was also observed in NK cells, infiltrating in human and murine lung cancer [25].…”
Section: Canonical Cb1 and Cb2 Expression In Nk Cellsmentioning
confidence: 63%
“…Flow cytometry and fluorescent microscopy analysis confirmed that NK cells express high CB2 protein levels, albeit showing a considerable variability among donors [22]. A similarly high CB2/CB1 ratio was also observed in NK cells, infiltrating in human and murine lung cancer [25].…”
Section: Canonical Cb1 and Cb2 Expression In Nk Cellsmentioning
confidence: 63%
“…Heterotopic tumor models are frequently used to investigate ways of influencing the TME. Recent publications showcase the use of the KP cell line as means to examine the possibility of switching a "cold" tumor into a "hot" tumor [49,50]. In this context, our group showed an improved response to PD-1 therapy in mice bearing KP cell tumors in which the cannabinoid-receptor 2 was absent in the TME [49].…”
Section: Discussionmentioning
confidence: 76%
“…Recent publications showcase the use of the KP cell line as means to examine the possibility of switching a "cold" tumor into a "hot" tumor [49,50]. In this context, our group showed an improved response to PD-1 therapy in mice bearing KP cell tumors in which the cannabinoid-receptor 2 was absent in the TME [49]. In MC38 tumors, the depletion of CD4 + T cells, CD25 + (T regs), or macrophages reduced tumor growth and supported PD-1 therapy [35].…”
Section: Discussionmentioning
confidence: 99%
“…Single cell suspensions of human esophageal mucosal biopsies were prepared according to digestion procedure published for dissected tumor tissue with minor modifications ( 27 , 28 ). Using surgical scissors, 2 fresh biopsies (proximal and distal) per patient were cut into small pieces, and afterwards digested with DNase I (160 U/mL; Worthington) and collagenase (4.5 U/mL; Worthington) for 20 min at 37°C, while rotating at 750 rpm.…”
Section: Methodsmentioning
confidence: 99%